DETERMINAN SUKU BUNGA PASAR UANG ANTAR BANK DI INDONESIA - Utami, Dyah (JEJAK: Jurnal Ekonomi dan Kebijakan, 2012)
Interbank money market (interbank) or often called the Interbank Call Money is one of the important means to encourage the development of money markets.Interbank money market is interest rate which is determined by the bank that needs loan. It also means that the interest rate which is charged to the banks that borrow some money in the interbank money market because of PUAB publishing. This study aims to analyze the determinants of the interbank money market in Indonesia. The variables in this study are the Singapore Interbank offered rate (SIBOR), SBI interest rates, and exchange rates. The results show that SIBOR has positive effect on the interest rate of Interbank Call Money, SBI has negative effect to the rates of Interbank Call Money, and the exchange rates has a positive effect to the rates of Interbank Call Money, and SIBOR, SBI, and the exchange rate at the same time affects the rates of Interbank Call Money.Pasar uang antar bank (PUAB) atau sering disebut dengan Interbank Call Money merupakan salah satu sarana penting untuk mendorong pengembangan pasar uang.Pasar uang antar bank sendiri adalah tingkat suku bunga yang ditentukan dan dikenakan oleh pihak bank kepada bank yang melakukan pinjaman di pasar uang antar bank atas penerbitan PUAB. Penelitian ini bertujuan untuk menganalisis determinan PUAB di Indonesia. Adapun variabel yang mempengaruhi dalam penelitian ini adalah Singapore Interbank offered rate (SIBOR), Suku bunga SBI, dan kurs. Hasil penelitian menunjukan bahwa SIBOR berpengaruh positif terhadap tingkat suku bunga PUAB, SBI berpengaruh negative terhadap suku bunga PUAB, dan Kurs berpengaruh positif terhadap suku bunga PUAB, serta secara bersama SIBOR, SBI, dan Kurs mempengaruhi tingkat suku bunga PUAB.Â